Child poverty - a discussion on conceptualization and measurement. A Portuguese case study - Amélia Bastos (European Regional Science Association (ERSA), 2001)
This work deals with child poverty. Although it is a very topical issue, it is scarcely studied by the social scientists. The analysis of this problem normally appears as a sub-product of poverty. In fact the living conditions of children cannot be divorced from the family context. Nevertheless poverty at the level of children displays its own specific features, along with a number of consequences that justify the study of childhood poverty per se. In this work the child is assumed to be a statistical unit. Therefore, from the economic point of view, the analysis of its living conditions is undertaken by considering those elements felt to be more important to its well being. In this context, a direct methodology has been adopted to directly evaluate child poverty. The paper begins by presenting the objectives of the study, as well the methodology used. The second and third points address questions related to conceptualization of the phenomenon and its quantification. This analysis allows one to make an initial distinction between the overall poverty problem and that of child poverty. The conclusions prove that, although they are interconnected, the two phenomena could be studied autonomously. The fourth point synthesizes the results of an empirical analysis of the phenomenon reviewed. To perform this analysis, a survey on the well-being of children living in an urban area was conducted through a sampling process, and its results were subsequently modeled. An econometric methodology was used to accurately verify the conclusions arising from the survey. The techniques employed are not that common in poverty studies.
Keywords: 330